Integrating psychiatry and family medicine in the management of somatic symptom disorders: Diagnosis, collaboration, and communication strategies - Victor Ajluni (Journal of General and Family Medicine)
Abstract Somatic symptom disorders (SSDs) present a complex interplay of physical and psychological factors, necessitating an integrative approach to diagnosis and management. This article explores the collaborative efforts between family medicine and psychiatry in addressing SSDs, emphasizing the importance of a multidisciplinary strategy for comprehensive patient care. Effective diagnosis involves recognizing the significance of both somatic symptoms and the patient's psychological response, with tools like structured clinical interviews and self‐report questionnaires playing crucial roles. Management strategies include psychotherapeutic interventions such as cognitive behavioral therapy (CBT), pharmacological treatments, and lifestyle modifications, all tailored to the patient's needs. Communication strategies are vital in validating patients' experiences while addressing underlying psychiatric issues. Techniques such as active listening, biopsychosocial framing, and the teach‐back method foster trust and improve treatment adherence. Cultural considerations and the use of interpreters enhance communication with diverse patient populations. Training programs for healthcare providers further improve competency in managing SSDs. This integrative approach aims to enhance patient outcomes by addressing the multifaceted nature of SSDs through collaborative care, effective communication, and comprehensive treatment planning.